The Patterns of N/P/K Stoichiometry of Indonesian Soybean Varieties in the Dryland Environment - Fatkhunnisa, Ratu; Santosa, Edi; Supijatno (Journal of Tropical Crop Science, 2025)
Soybeans are among the best plant-based sources of protein. However, a high intake of rich potassium legumes such as soybean could have negative impacts on people who are sensitive to high potassium. A study on NPK stoichiometry of the most popular Indonesian soybean varieties was conducted as a preliminary evaluation to develop low-potassium soybeans. The experiment was conducted at Cikabayan Experimental Station, IPB University, from January to April 2024. The field experiment was arranged in randomized block design using 12 soybean varieties: “Anjasmoro”, “Deja 2”, “Dena 1”, “Dering 1”, “Denasa 1”, “Denasa 2”, “Dering 3”, “Devon 1”, “Devon 2”, “Grobogan”, “Mallika”, and “Slamet”. Results showed that “Slamet” produced the highest stover while “Anjasmoro” was the lowest. “Slamet”, “Dering 1”, and “Mallika” produced the highest bean production per hectare (3.75-4.73 t ha- 1). N uptake was higher than P, and K. Seed of “Dena 1” had the lowest K content, while the highest was “Denasa 1”. The stoichiometric ratios of N/P, N/K, P/K showed different values according to varieties. Thus, decreasing the K level in seed could be done by selecting a low K variety.